RELATIONSHIP OF TEMPERATURE, HUMIDITY AND LIGHTING WITH FLY DENSITY IN PANCUR BATU MARKET, PANCUR BATU DISTRICT, DELI SERDANG REGENCY - Nanda, Meutia; Marunduri, Ridho Afdal; Signora, Khalisa Aisyah; Sinantin, Ipak; Sari, Kurnia Permata (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
Flies are one of the mechanical vectors of disease commonly found in market environments. Environmental factors such as temperature, humidity, and lighting are suspected to influence the density of flies. This study aims to determine the relationship between temperature, humidity, and lighting with fly density at Pancur Batu Market, Pancur Batu District, This study involved a sample of 85 stalls selected through purposive sampling from five types of vendor areas (chicken, fish, meat, vegetables, and fruit). Fly density was measured using Pagoda fly paper traps, while temperature, humidity, and lighting were measured using a thermohygrometer and a luxmeter. Data analysis was conducted using the chi-square test in SPSS software, The results showed that most locations 69 stalls (81.2%) had high fly density. Temperature did not meet the standard at 73 stalls (85.9%), humidity met the standard at 31 stalls (36.5%), and lighting met the standard at 61 stalls (71.8%). Only humidity was significantly associated with fly density (p = 0.012), whereas temperature (p = 0.848) and lighting (p = 1.000) showed no significant relationship with fly density at Pancur Batu Market. Humidity is the most influential environmental factor affecting fly density at Pancur Batu Market. Therefore, managing humidity and improving market cleanliness should be prioritized to reduce the fly population and the risk of disease transmission.